2014
DOI: 10.3892/or.2014.3131
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin induces drug resistance and expression of the novel CD44st via NF-κB in human breast cancer MCF-7 cells

Abstract: Abstract. CD44, a major receptor for hyaluronan (HA), is a member of a class of adhesion molecules of unknown classification involved in cell proliferation, differentiation, migration, angiogenesis, and the presentation of specific cytokines to the corresponding receptors as well as in cell signaling transduction. It has recently been discovered that CD44, a marker of tumor stem cells, is involved in the drug resistance and invasion of multiple types of tumors. The 20 exons in the CD44 gene that are alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 23 publications
6
30
1
Order By: Relevance
“…At present, the precise mechanism by which doxorubicin upregulates DR transcripts is not clear but it may involve activation of NF-κB pathway. As a shared transcription factor for all four DRs, NF-κB was shown to be activated in multiple cancer types in response to doxorubicin treatment155152. Nonetheless, the ability of doxorubicin to upregulate DRs in cardiomyocytes provides critical insight into the molecular mechanisms of the adverse drug reaction.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the precise mechanism by which doxorubicin upregulates DR transcripts is not clear but it may involve activation of NF-κB pathway. As a shared transcription factor for all four DRs, NF-κB was shown to be activated in multiple cancer types in response to doxorubicin treatment155152. Nonetheless, the ability of doxorubicin to upregulate DRs in cardiomyocytes provides critical insight into the molecular mechanisms of the adverse drug reaction.…”
Section: Discussionmentioning
confidence: 99%
“…However, the DNA damage induced by doxorubicin activates the NF-κB pathway, leading to doxorubicin resistance in cancer cell lines, including in breast cancer cells15161718.…”
mentioning
confidence: 99%
“…Those studies showed that hyaluronan upregulates the expression of MMP2 and MMP9 by interacting with CD44st, and thus increases the aggressiveness of MCF-7 cells. The CD44st gene is probably also associated with aggressiveness, metastasis, and prognosis of breast cancer [7][8][9].…”
Section: Introductionmentioning
confidence: 99%